Commodities and Culture in the Colonial World - Chaudhuri, Supriya, author.
1 online resource (xiv, 208 pages)
Keywords: "Commodity culture and colonialism are intimately related and mutually constitutive. The desire for commodities drove colonial expansion at the same time that colonial expansion fuelled technological invention, created new markets for goods, displaced populations, and transformed local and indigenous cultures in dramatic and often violent ways. This book analyses the transformation of local cultures in the context of global interaction in the period 1851-1914. By focusing on episodes in the social and cultural lives of commodities, it explores some of the ways in which commodities shaped the colonial cultures of global modernity. Chapters by experts in the field examine the production, circulation, display and representation of commodities in various regional and national contexts, and draw on a range of theoretical and disciplinary approaches. An integrated, coherent and urgent response to a number of key debates in postcolonial and Victorian studies, world literature and imperial history, this book will be of interest to researchers with interests in migration, commodity culture, colonial history, and transnational networks of print and ideas. "--Provided by publisher.